2017
DOI: 10.17576/jskm-2017-1502-24
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Testing Otoliths and Semicircular Canals Function using VEMPs and vHIT in Malaysian Children

Abstract: Early identification of any vestibular dysfunction and balance problem in children is crucial for their general well-being. However the identification process, could be challenging and difficult as compared to adults. We conducted a preliminary study to review our initial experience with ocular and cervical vestibular evoked myogenic potentials (oVEMPs and cVEMPs), video head impulse test (vHIT) and Bruininks Oseretsky Test of Motor Proficiency II (BOT-2) on healthy children and also to determine the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…A VOR gain of 0.8-1 was considered normal for the lateral semicircular canal whilst a VOR gain of 0.6-0.8 was the norm for the vertical canals. Recent studies (33,34) indicate that vertical canal gains are lower in the pediatric population than in adults similar to what we have also found using similar equipment in children with normal vestibular function (35). Saccades, rather than VOR gain, were deemed as pathological weakness as studies have shown that saccades can occur with normal VOR gain in vestibular hypofunction (36,37).…”
Section: Audiovestibular Quantificationsupporting
confidence: 87%
See 1 more Smart Citation
“…A VOR gain of 0.8-1 was considered normal for the lateral semicircular canal whilst a VOR gain of 0.6-0.8 was the norm for the vertical canals. Recent studies (33,34) indicate that vertical canal gains are lower in the pediatric population than in adults similar to what we have also found using similar equipment in children with normal vestibular function (35). Saccades, rather than VOR gain, were deemed as pathological weakness as studies have shown that saccades can occur with normal VOR gain in vestibular hypofunction (36,37).…”
Section: Audiovestibular Quantificationsupporting
confidence: 87%
“…One difficulty in children is the standardization of norms. We have explained about these norms in our Methods section (33)(34)(35). The average VOR gain in our series in all canals was mostly normal in the 4 different groups that we have also found in a previous study (5) suggesting that VOR gain is largely preserved in pediatric third window disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A portable vHIT device (GN Otometrics, ICS Impulse, USA) was used to assess the VOR function of HIMP and SHIMP as previously described. 9 , 12 , 20 , 21 The vHIT consists of a pair of light-weight video goggles and an infra-red video camera on the right side of the frame, equipped with a head-mounted red-laser beam. The goggle was secured on the subject’s head using an adjustable strap to avoid slippage during head impulses.…”
Section: Methodsmentioning
confidence: 99%
“…This study used testing protocols, stimulus recording techniques and parameters recommended by past studies ( 16 , 22 , 23 ). The 750 Hz TB acoustic stimuli (rise/fall time 0 ms, plateau 2.67 ms, stimulation rate 5/s) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The recording was done within a 50 ms time window, with 80 stimuli averaged for each run. The EMG signal was amplified and band-passed filtered between 20 Hz and 500 Hz ( 22 ).…”
Section: Methodsmentioning
confidence: 99%